Mediating effects of creative home environment and self-directed learning ability on the relationship between creative personality and creative achievement intention - Lee, Ga Hyung (Creativity Studies, 2024)
This study verified the mediating effects of creative home environment and self-directed learning ability on the relationship between creative personality and creative achievement intention of university students. Creative personality was set as independent variable, creative home environment and self-directed learning ability as mediating variables, and creative achievement intention as dependent variable. This study was conducted from June 10 to July 10, 2019 in Seoul, South Korea, and the participants were 587 university students. Data was collected through an online–offline test and analysed using SPSS Statistics 25.0. Creative personality affected creative achievement intention through the medium of creative home environment. However, self-directed learning ability had no mediating effect in the influence of creative personality on creative achievement intention. Therefore, creative home environment is important to improve the creative achievement intention of university students. Further, that the family’s environmental support affects the creative achievement intention to express creativity in course of development bears implications for parent education.